Pengaruh Sales Growth dan Intensitas Modal Terhadap Tax Avoidance dengan Kepemilikan Institusional sebagai Variabel Moderasi pada Perusahaan Sektor Barang Baku yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Arifah Dwi Wahyuni; Mulyadi Mulyadi; Panata Bangar Hasioan Sianipar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The purpose of this study is to examine the effect of sales growth and capital intensity on tax avoidance, either directly or through institutional ownership variables as moderation. This study uses quantitative research methods with the type of data, namely secondary data, obtained from annual financial reports. The population and samples used in this study are annual financial reports on raw goods sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period with a sampling technique, namely purposive sampling technique. The results of the study revealed that sales growth has no effect on tax avoidance, capital intensity affects tax avoidance, institutional ownership does not moderate the effect of sales growth on tax avoidance, and institutional ownership moderates the effect of capital intensity on tax avoidance.